IMPLEMENTASI MODEL GEMA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Diah Arum Ningsih; Diani Ayu Pratiwi (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Critical thinking skills are needed and influential in the teaching and learning process, because they are one of the factors that can influence the success of activities and student learning outcomes in the classroom. However, based on the facts that occur in the field, critical thinking skills and student activity are still low which results in low student learning outcomes. Based on these problems, the Gema combination model is used in this study as one of the best solution or treatments. This research was conducted to describe and analyze students' critical thinking activities in the learning process. The research was conducted using Classroom Action Research (CAR), with research subjects in class IVA at SDN Kelayan Selatan 10 Banjarmasin. The data obtained in this study are qualitative data taken from student activities, and quantitative data taken through measurement techniques with written tests. The results of the study showed an increase in each meeting in the aspects of students' critical thinking skills who were in the criteria of being skilled and highly skilled achieving results of 89% of the total number of students. So it can be concluded that the activity of students' critical thinking skills at each meeting increases and the hypothesis can be accepted and the research can be said to be successful. It is hoped that this research can be used as a solution and material for consideration by teachers in using learning models to improve critical thinking skills and student activities which also affect the increase in student achievement